2018
DOI: 10.1002/lary.27308
|View full text |Cite
|
Sign up to set email alerts
|

Are Perioperative Antibiotics Necessary During Direct Microlaryngoscopy?

Abstract: Objectives/Hypothesis There are currently no established recommendations for the use of perioperative antibiotics (PAs) to prevent surgical site infections (SSIs) for direct microlaryngoscopy (DML). This study examined the incidence of SSI in patients undergoing DML with and without PAs. Study Design Retrospective, multi‐institutional chart review. Methods A retrospective, multi‐institutional chart review was performed at four tertiary referral academic medical centers. Patients undergoing DML from 2010 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Our findings are supported by a recent multi‐institutional study by Yetzke et al, which evaluated the efficacy of one‐time perioperative antibiotics prior to surgical incision in the prevention of SSI in phonomicrosurgery and demonstrated no difference in SSI rates . Interestingly, they found an overall SSI rate of only 0.12%, which is lower than the overall SSI rate in most clean‐contaminated cases and also lower than the 3.2% rate of SSI found in our study .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are supported by a recent multi‐institutional study by Yetzke et al, which evaluated the efficacy of one‐time perioperative antibiotics prior to surgical incision in the prevention of SSI in phonomicrosurgery and demonstrated no difference in SSI rates . Interestingly, they found an overall SSI rate of only 0.12%, which is lower than the overall SSI rate in most clean‐contaminated cases and also lower than the 3.2% rate of SSI found in our study .…”
Section: Discussionsupporting
confidence: 89%
“…The Centers for Disease Control (CDC) has stated that perioperative antibiotic prophylaxis is not indicated for clean, nonprosthetic‐associated procedures, as defined by international guidelines . More recently, the CDC has moved away from recommending perioperative antibiotic prophylaxis for all clean‐contaminated procedures, including those on the aerodigestive tract, to “only when indicated based on clinical practice guidelines.” Unfortunately, there are no clinical practice guidelines for laryngeal procedures for benign diseases . Further, in the updated 2017 recommendations, the CDC recommends against the use of postoperative antibiotics in clean and clean‐contaminated procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Additionally, two studies examining a range of direct laryngoscopy and microlaryngoscopy procedures have shown no significant difference in SSI related to presence or absence of perioperative antibiotic use. 8,9 Our analysis demonstrated inconsistency at our institution between best practice guidelines and perioperative antibiotic use in low-risk head and neck procedures. Almost one-third of these patients received unnecessary perioperative antibiotics.…”
Section: Discussionmentioning
confidence: 92%
“…5,6 However, there are certain otolaryngology (ENT) procedures with low surgical site infection (SSI) risk for which there is negligible benefit from perioperative antibiotic administration. [7][8][9] The objective of this evaluation was to describe antibiotic use and adherence to best practices in lowrisk head and neck procedures for which antibiotic prophylaxis is not indicated within our institution.…”
Section: Introductionmentioning
confidence: 99%